Rotavirus infections in the pediatric population: a comparative study of pre-COVID and COVID-19 pandemic periods - Öztelcan Gündüz, Bahar; Kutlutürk, Kazım; Ünay, Bülent (Frontiers in Public Health, 2025)
BackgroundThis study investigates the impact of the COVID-19 pandemic on the incidence and clinical outcomes of rotavirus infections in the pediatric population.MethodsThis retrospective study was conducted at the Pediatrics Clinic of Gülhane Research and Training Hospital, analyzing data from the pre-COVID-19 period (January 1, 2017 – January 1, 2020) and during the COVID-19 pandemic period (March 11, 2020 – August 31, 2022). Patient data, including demographic characteristics, presenting complaints, laboratory results, and hospitalization status, were collected from hospital records. Statistical comparisons were made to evaluate changes in rotavirus infection patterns between the two examined periods.ResultsThe data of a total of 3,915 pediatric patients with diarrhea were included, with 468 (6.8%) testing positive for rotavirus. Three hundred and forty of these cases (72.6%) were detected during the COVID-19 pandemic period, while 128 cases (27.4%) were detected before the pandemic period. The median age of the patients was 2 years, while 62.7% were under 2 years of age. Significant differences were found between the pre-COVID-19 and COVID-19 periods in terms of the number of emergency department visits (p = 0.003), the duration of emergency observations (p = 0.001) and the rates of patient visits from urban or rural centers (p = 0.001). Laboratory parameters, including blood sodium levels (p = 0.02), neutrophil counts (p = 0.02), base excess (p = 0.03), and bicarbonate levels (p = 0.05), also showed significant differences. Factors influencing hospitalization were found to be emergency department observation time (hours) with an OR of 0.91, 95% CI (0.867–0.974) (p = 0.005), blood glucose levels with an OR of 1.03, 95% CI (1.02–1.05) (p = 0.002), serum potassium levels with an OR of 2.36, 95% CI (1.14–4.87) (p = 0.02), and CRP levels with an OR of 1.02, 95% CI (1.01–1.03) (p = 0.006).ConclusionThe results of this study emphasize the need for targeted interventions to manage rotavirus infections, particularly in the context of ongoing public health challenges. Understanding the COVID-19 pandemic’s effects on rotavirus epidemiology is crucial for developing effective strategies to mitigate severe outcomes in vulnerable pediatric populations.